2021
DOI: 10.7150/jca.55511
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Body-Weight Signaling Players: GDF15, GFRAL and RET and their clinical relevance in Gastric Cancer

Abstract: The existence, the functional role and clinical relevance of GDF15 and its signaling through a GFRAL/RET-dependent complex in gastric cancer (GC) and other human tumors remain to be elucidated, despite the widespread recognition of obesity as an important cancer-predisposing factor. Therefore, we aimed to analyze the expression levels of GDF15, GFRAL and RET in GC tissues in relation to each other and clinicopathological features, including patient survival, in order to establish a potential implication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Recent evidence showed that tumor grading is related to GDF15 and GFRAL expression, and Lauren's classification is related to GFRAL expression in gastric cancer patients 53 . Inconsistently, we revealed that GDF15 and GFRAL protein expressions might not be good prognostic factors for patients with gastric cancer (Tables 1 and 3).…”
Section: Discussionmentioning
confidence: 54%
“…Recent evidence showed that tumor grading is related to GDF15 and GFRAL expression, and Lauren's classification is related to GFRAL expression in gastric cancer patients 53 . Inconsistently, we revealed that GDF15 and GFRAL protein expressions might not be good prognostic factors for patients with gastric cancer (Tables 1 and 3).…”
Section: Discussionmentioning
confidence: 54%
“…KPCA is targeted by HF drug midostaurin, and is involved in the significantly enriched RET signalling pathway, together with GFRA1 and RET ( Appendix Table S10 ). The RET receptor is activated by GFRA1 and is needed for GDF15 signalling 56 , where GDF15 concentrations are predictive of HF outcome 57,58 . GDF15 has also been shown to associate with stroke, bleeding, and mortality in AF patients 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CDK9 was determined using IHC assays according to the protocol described in Buchholz et al study [ 16 ]. In the beginning, standardization and optimization of the IHC method were performed on a recommended tissue, based on the antibody datasheet and reference sources (The Human Protein Atlas: https://www.proteinatlas.org ; [ 17 ]).…”
Section: Methodsmentioning
confidence: 99%
“…The results from the CDK9 group have been published in our recent article and are available on request from the corresponding author; reference [ 16 ]. The data presented in this study are available on request from the corresponding author.…”
mentioning
confidence: 99%